The Influence of Online Customer Reviews, Content Marketing, and Brand Image on The Purchase Decision: Empirical Study of Erigo Products on TikTok Shop - Susanti, Aprilia; Muzdalifah, Laily; Larassaty, Ayu; Violita, Cynthia (Manunggal Halim Jaya, 2026)
This research aims to analyze the influence of Online Customer reviews, Content Marketing, and Brand Image on purchasing decisions for Erigo products at TikTok Shop. This study uses quantitative research and purposive sampling. From the results of this test, it can be concluded that Online Customer reviews do not significantly affect purchasing decisions. Content Marketing also does not have a significant effect on purchasing decisions. Brand image has a significant effect on purchasing Erigo products at the TikTok Shop.